Crystal structure of N-cyclopropyl-3-hydroxy-4-methoxybenzamide, C11H13NO3 - Tong Hongjuan; Xu Xiaona; Zhu Zhoujing; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C11H13NO3, monoclinic, P21/n (no. 14), a = 8.0478(3) Å, b = 9.8093(4) Å, c = 13.1602(5) Å, β = 104.712(2)°, V = 1004.85(7) Å3, Z = 1, Rgt(F) = 0.0395, wRref(F2) = 0.1010, T = 170 K.